Expression of social skills of a child with autism spectrum disorder. Case analysis - Jurevičienė, Margarita; Šostakienė, Nijolė (Social Welfare: Interdisciplinary Approach, 2014)
Profound deficit in social reciprocity skills is the core, underlying feature of the autism spectrum disorders (ASD). It is not doubted that social skills condition the quality of person’s social functioning and management of social situations and has enormous impact on individual’s personal and social life. Thus, social skills are behaviors that must be taught, learned, however, in planning the development of social skills at first it is important to identify individual powers of a child with autism spectrum disorder and problematic fields in the system child-family-school. In the present research the expression of social skills of a child with autism spectrum disorder is revealed through the following structural components: 1) interaction skills; 2) communication skills 3) participation skills 4) emotional skills 5) social cognition skills with the method of case analysis, combining content analysis of interview and observation data. The research data have been collected with the method of observation and purposeful semi-structured interview; methods of data analysis: interpretative content analysis of the texts of observation and interview.